Answer:
[tex]P(x) = -\frac{11}{12}(x+2)(x+1)(x-3)[/tex]
Step-by-step explanation:
Zeros of a function:
Given a polynomial f(x), this polynomial has roots [tex]x_{1}, x_{2}, x_{n}[/tex] such that it can be written as: [tex]a(x - x_{1})*(x - x_{2})*...*(x-x_n)[/tex], in which a is the leading coefficient.
Zeros of -2,-1, and 3
This means that:
[tex]P(x) = a(x - (-2))(x - (-1))(x - 3) = a(x+2)(x+1)(x-3)[/tex]
Passes through the point (2, 11).
This means that when [tex]x = 2, P(x) = 11[/tex]. We use this to find the leading coefficient.
[tex]P(x) = a(x+2)(x+1)(x-3)[/tex]
[tex]a(2+2)(2+1)(2-3) = 11[/tex]
[tex]-12a = 11[/tex]
[tex]a = -\frac{11}{12}[/tex]
So the polynomial is:
[tex]P(x) = -\frac{11}{12}(x+2)(x+1)(x-3)[/tex]